5‐azacytidine inhibits nonsense‐mediated decay in a MYC‐dependent fashion. Issue 12 (15th October 2014) - Bhuvanagiri, Madhuri; Lewis, Joe; Putzker, Kerstin; Becker, Jonas P; Leicht, Stefan; Krijgsveld, Jeroen; Batra, Richa; Turnwald, Brad; Jovanovic, Bogdan; Hauer, Christian; Sieber, Jana; Hentze, Matthias W; et al.
Abstract Nonsense‐mediated RNA decay (NMD) is an RNA‐based quality control mechanism that eliminates transcripts bearing premature translation termination codons (PTC). Approximately, one‐third of all inherited disorders and some forms of cancer are caused by nonsense or frame shift mutations that introduce PTCs, and NMD can modulate the clinical phenotype of these diseases. 5‐azacytidine is an analogue of the naturally occurring pyrimidine nucleoside cytidine, which is approved for the treatment of myelodysplastic syndrome and myeloid leukemia. Here, we reveal that 5‐azacytidine inhibits NMD in a dose‐dependent fashion specifically upregulating the expression of both PTC‐containing mutant and cellular NMD targets. Moreover, this activity of 5‐azacytidine depends on the induction of MYC expression, thus providing a link between the effect of this drug and one of the key cellular pathways that are known to affect NMD activity. Furthermore, the effective concentration of 5‐azacytidine in cells corresponds to drug levels used in patients, qualifying 5‐azacytidine as a candidate drug that could potentially be repurposed for the treatment of Mendelian and acquired genetic diseases that are caused by PTC mutations.